1998
DOI: 10.1002/(sici)1098-2272(1998)15:1<103::aid-gepi8>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

FRAXA and FRAXE prevalence in patients with nonspecific mental retardation in the Hellenic population

Abstract: Mutations at FRAXA and FRAXE loci are due to expansions of a CGG trinucleotide repeat and are characterized by mental retardation. Here we report a pilot screening survey by means of cytogenetic and molecular methods of 433 unrelated retarded individuals and their parents of Hellenic origin coming from various parts of Greece and Cyprus. The purpose of the study was to estimate the frequency of FRAXA mutation in individuals with nonspecific mental retardation without family history and phenotypic stigmata in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Employing the DNA diagnostic methods, another report from Southern India revealed a frequency of 7%, comparable to our results [Baskaran et al, 1998]. However, we cannot compare our results with those reported for most other Western institutionalized populations, which included all unexplained MR cases in their study samples [Meadows et al, 1996;Mila et al, 1997;Elbaz et al, 1998;Syrrou et al, 1998;Crawford et al, 1999;Pang et al, 1999;Patsalis et al, 1999]. Considering the stringent selection criteria employed in this study, the overall frequency of FXS in India may be very similar to that reported for other Western and Asian populations [Patsalis et al, 1999].…”
Section: Discussionsupporting
confidence: 84%
“…Employing the DNA diagnostic methods, another report from Southern India revealed a frequency of 7%, comparable to our results [Baskaran et al, 1998]. However, we cannot compare our results with those reported for most other Western institutionalized populations, which included all unexplained MR cases in their study samples [Meadows et al, 1996;Mila et al, 1997;Elbaz et al, 1998;Syrrou et al, 1998;Crawford et al, 1999;Pang et al, 1999;Patsalis et al, 1999]. Considering the stringent selection criteria employed in this study, the overall frequency of FXS in India may be very similar to that reported for other Western and Asian populations [Patsalis et al, 1999].…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence 1/3,460 (CI 1/7,143-1/1,742) estimated here for FRAXA syndrome in a white male population is in agreement with that determined in previous studies (Murray et al 1996;Turner et al 1996;de Vries et al 1997;Morton et al 1997;Syrrou et al 1998). On the basis of this estimate, we project the prevalence among females to be ∼1/9,000, assuming that ∼50% of female full-mutation carriers exhibit the syndrome (Rousseau et al 1994) and that the frequency of male and female full-mutation carriers is equal (Sherman 1995a).…”
Section: Prevalencesupporting
confidence: 92%
“…Since the advent of molecular testing, we as well as others have examined the prevalence of the fragile X syndrome among males with specific cognitive or behavioral problems and have extrapolated the estimate to the general population. This has been done primarily for males of mostly northern European descent, and the prevalence was estimated at 1/6,000 to 1/4,000 males in the general population [Murray et al, 1996; Turner et al, 1996; Morton et al, 1997; de Vries et al, 1997; Syrrou et al, 1998; Crawford et al, 1999; Youings et al, 2000]. In our previous report, we estimated the prevalence of the fragile X syndrome as well as the other forms of the FMR1 alleles in a Caucasian and African‐American population of children in special education classes in the public school system residing in the four counties of metropolitan Atlanta, Georgia [Crawford et al, 1999].…”
Section: Introductionmentioning
confidence: 99%